PENGAWASAN DINAS PERTAMBANGAN DAN ENERGI TERHADAP USAHA PERTAMBANGAN GRANIT (STUDI KASUS PT.KAWASAN DINAMIKA HARMONITAMA KABUPATEN KARIMUN TAHUN 2012-2014) - Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Supervision is very important in all work, especially in government, lack of sovervisions is a phenomenon that is polemical and losses for varios parties, this phenomenon also occurs Karimun, where supervision of the Department of Mines and Energy Against Granite Mining less than the maxumum. Because there are many mining activities are carried out not in accordance with the provisions in force at the time get a mining license in the District of Karimun. Granite.The purpose of this study was to determine the mechanism of supervision conducted by the government of Karimun Regency on granite mining business and knowing the obstacles that cause lack of oversight conducted by the Department of mines and Energy Informants in this study is the Head of Mining and Energy Karimun, Legislators Karimun Regency, Head of Supervision and Control, Menagers Operations PT Kawasan Dynamics Harmonitama, Secretary of the Environment Agency Karimun and society, Data Collection Techniques with interviews to determine the extent of oversight Against Mining and Energy Mining Granite. Qualitative data analysis technique that is performed on the data, in this case the qualitative data in the form of information, a description in the form of prose language other then linked to the data to obtain clarity on the truth.Results from this study, Monitoring the Department of Mines and Energy Karimun against the mining of granite have been implemented in accordance with existing conduct surveillance, then the next factor less accuracy officer at the time oversight and lack of firmness sanctions applied so as not to make the miners fear or deterrent.Keywords : Control, the Department of Mines and Energy, Business